Exploring Virtual Reality-Induced Anxiety in Iatrophobia: A Pilot Study for Future Exposure Therapy - Revelo-Aguilar Fabian; Miro-Amarante Lourdes; Gomez-Rodriguez Francisco (IEEE Access, 2025)
This pilot study explores the feasibility of using Virtual Reality (VR) to simulate medically related environments that elicit anxiety responses in individuals with iatrophobia—a specific phobia characterized by an intense fear of medical professionals and procedures. Rather than providing a therapeutic intervention, the aim is to validate the capacity of VR-based scenarios to induce physiological and emotional reactions associated with medical anxiety, thereby laying the groundwork for future therapeutic applications. Ten participants—five with self-reported iatrophobia and five without—were exposed to a series of VR scenarios simulating clinical settings, including a waiting room, a medical consultation, and a diagnostic procedure. The study was conducted at the Ecuadorian Institute of Social Security (IESS), Ambato Hospital, Ecuador. Physiological responses, including heart rate and electrodermal activity, were measured and analyzed using statistical methods. The results demonstrate significant differences between the experimental and control groups, with individuals with Iatrophobia exhibiting heightened anxiety responses in VR environments. Furthermore, correlation analysis reveals a strong positive association between heart rate and electrodermal response, indicating the reliability of these physiological indicators in assessing anxiety levels. The study also discusses the implications of these findings for phobia treatment and highlights future research directions, including the integration of advanced VR technologies and exploring VR’s applicability in treating other specific phobias and anxiety disorders. These findings support the use of VR for eliciting controlled emotional responses in medical contexts, which may inform the design of future exposure-based interventions for iatrophobia and other medical-related phobias.